One-Side Derived Categories of Pre-Strict $P$-Semi-Abelian Categories (Journal of Mathematical Study, 2021)
In this paper, we study a class of $P$-semi-abelian categories, as well as leftand right cohomological functors. Then we establish the corresponding one-side derivedcategories.
Keywords: $P$-semi-abelian category; cohomological functor; one-side derived category.